Drug Coated Balloon-Only Strategy in De Novo Lesions of Large Coronary Vessels - Mark Rosenberg; Matthias Waliszewski; Florian Krackhardt; Kenneth Chin; Wan Azman Wan Ahmad; Giuseppe Caramanno; Diego Milazzo; Amin Ariff Nuruddin; Houng Bang Liew; Oteh Maskon; Angela Bento; Jean-Christophe Macia; et al. (Journal of Interventional Cardiology, 2019)
Objectives. We analyzed the efficacy of drug coated balloons (DCB) as a stand-alone-therapy in de novo lesions of large coronary arteries. DCBs seem to be an attractive alternative for the stent-free interventional treatment of de novo coronary artery disease (CAD). However, data regarding a DCB-only approach in de novo CAD are currently limited to vessels of small caliber. Methods. By means of propensity score (PS) matching 234 individuals with de novo CAD were identified with similar demographic characteristics. This patient population was stratified in a 1:1 fashion according to a reference vessel diameter cut-off of 2.75 mm in small and large vessel disease. The primary endpoint was the rate of clinically driven target lesion revascularization (TLR) at 9 months. Results. Patients with small vessel disease had an average reference diameter of 2.45 ± 0.23 mm, while the large vessel group averaged 3.16 ± 0.27 mm. Regarding 9-month major adverse cardiac event (MACE), 5.7% of the patients with small and 6.1% of the patients with large vessels had MACE (p=0.903). Analysis of the individual MACE components revealed a TLR rate of 3.8% in small and 1.0% in large vessels (p=0.200). Of note, no thrombotic events in the DCB treated coronary segments occurred in either group during the 9-month follow-up. Conclusions. Our data demonstrate for the first time that DCB-only PCI of de novo lesions in large coronary arteries (>2.75 mm) is safe and as effective. Interventional treatment for CAD without permanent or temporary scaffolding, demonstrated a similar efficacy for large and small vessels.